The impact of COVID-19 pandemic on Moroccan firms’ performance: A pre- and post-crisis comparative analysis - Idrissi, Nabaouia; Mizani, Manal El; Charif, Ahmed; DARKAWI, Zakaria BEN; Makati, Safaa (Edelweiss Applied Science and Technology, 2025)
The health crisis linked to the COVID-19 pandemic has profoundly disrupted the global economic fabric, having a lasting impact on corporate performance. This article aims to assess the impact of this crisis on the financial performance of Moroccan companies. The analysis is based on two key indicators, return on assets (ROA) and return on equity (ROE), measured on a sample of Moroccan companies from various sectors. The Wilcoxon signed-rank test was applied to compare financial performance before and after the COVID-19 pandemic. Additionally, linear regression was performed to assess the impact of the health crisis on the financial performance of companies. Both the Wilcoxon signed-rank test and linear regression show that firm performance declined after the COVID-19 pandemic. These results reflect the fragility of certain companies in the face of exogenous shocks and underline the importance of strengthening their resilience through more appropriate management mechanisms. This work paves the way for future research incorporating governance variables as explanatory factors of organizational resilience.